Strategi Pelatihan Guru dan Siswa Model Pembelajaran Problem Based Learning (PBL) Terintegrasi Lesson Study untuk Melatihkan Kemampuan Berpikir Kritis pada Pembelajaran Biologi - Tenggarudin, Tenggarudin (Universitas Sebelas Maret, 2016)
This study aims to describe senior high school student’s critical thinking ability who has been taught through model of PBL integrated lesson study. This study is carried out in six stages: (1) preliminary study of learning condition; (2) the development of hypothetical strategies; (3) tryout in order to validate training strategy and prototype of PBL instruments; (4) modelling; (5) implementation; and (6) experiment in order to test the practicality and the effectiveness of training strategy. The teacher training strategy in this study is described in lesson study on the other hand, student training strategy is described in PBL learning in the classroom. PBL learning activity integrated lesson study is carried out for six cycle (six lesson plan). The results of the study shows that; (1) the implementation of PBL integrated in Lesson Study can improve student achievement in critical thinking, (2) student achievement in critical thinking for six cycle has improved from cycle to cycle. PBL barriers are mainly caused by limited of IT facilities and the study time allocation. The results showed that the teachers and students training strategy through model of PBL integrated lesson study can improve teacher's skills to design and manage PBL, improve students’ performance critical thinking.Keywords: training of teachers and students, PBL, lesson study